Krzysztof Wielecki, Kultura versus kultura masowa [Culture versus Mass Culture]. Warszawa: Narodowe Cenrum Kultury, 2024, 662 pages - Dancák, Pavol (Philosophy and Canon Law, 2024)
Krzysztof Wielecki, Kultura versus kultura masowa, 662 pp. Warszawa: Narodowe Cenrum Kultury, 2024